ANALISA PENGARUH VARIASI (% BERAT) MAGNESIUM DAN VARIASI TEMPERATUR OKSIDASI PADA PROSES ELECTROLESS PLATING ABU DASAR BATUBARA TERHADAP DENSITAS DAN POROSITAS BAHAN PROPELLER DARI KOMPOSIT ALUMINIUM – ABU DASAR BATUBARA - Seputro, Harjo; Prasetio, Budi (MEKANIKA: Jurnal Teknik Mesin, 2015)
The composite is a combination of two or more different materials on condition the bonding surfacebetween the two materials. One type of composites that much attention is metal matrix composites (KML). In thisstudy investigated how the influence of variations of Mg and temperature variations of oxidation on the density andporosity of the composite amplifier undergo a process of electroless plating with variation (% by weight) ofmagnesium 0,005, 0,010, and 0,015% and variations in temperature oxidation of 100, 200 and 300 C and at holdfor 3 hours, then made composite by Stir Casting casting method. Based on the average chart shows that increasingthe value of (% by weight) of magnesium and oxidation temperature 0C the density values further down, This iscaused by the imbalance between the weight magnesium particles moistened (coal bottom ash) during theelectroless plating process. Based on the results of testing the value of the highest density achieved at a temperatureof 3000C to oxidation (wt%) 0.005 Mg is equal to 2.609 gr/cm3. And the value of the lowest density is achieved at atemperature of 200 0C to oxidation (wt%) Mg 0,010 is equal to 2.406 g / cmKeywords: composite, electroless plating, stir casting, density-porosity.